Evaluation of Ba0.5Sr0.5Co0.8Fe0.2O3-d as a potential cathode for an anode-supported proton-conducting solid-oxide fuel cell - Lin, Y.; Ran, R.; Zheng, Y.; Shao, Zongping; Jin, W.; Xu, N.; Ahn, J. (Elsevier SA, 2008)
The potential application of Ba0.5Sr0.5Co0.8Fe0.2O3-d (BSCF) as a cathode for a proton-conducting solid-oxide fuel cell based on BaCe0.9Y0.1O2.95 (BCY) electrolyte was investigated. Cation diffusion from BCY to BSCF with the formation of a perovskite-type Ba2+-enriched BSCF and a Ba2+-deficient BCY at a firing temperature as low as 900 °C was observed, the higher the firing temperature the larger deviation of the A to B ratio from unit for the perovskites. Symmetric cell tests demonstrated the impurity phases did not induce a significant change of the cathodic polarization resistance, however, the ohmic resistance of the cell increased obviously. Anode-supported cells with the electrolyte thickness of ~50 µm were successfully fabricated via a dual-dry pressing process for the single-cell test. Under optimized conditions, a maximum peak power density of ~550 and 100 mW cm-2 was achieved at 700 and 400 °C, respectively, for the cell with the BSCF cathode layer fired from 950 °C. At 500 °C, the ohmic resistance is still the main source of cell resistance. A further reduction in membrane thickness would envisage an increase in power density significantly. © 2008 Elsevier B.V. All rights reserved.